Partial characterization and antimicrobial spectrum of inhibitory substances from marine Alteromonas - León, Jorge (1999)
Inhibitory substances produced by marine strains belonging to the genus Alteromonas spp. are partially characterized. Precipitation of raw extracts supernatans from strains N22.C and N11.6 with concentration saturants of ammonium sulfate and filtrates in columns Sephadex G-25 show the production of inhibitory substances (SI) of proteinacea nature. Other assays revealed that these substances have a wide spectrum of antibiotic activity against collection strains pathogens of fish, mollusks and crustaceans. Also, it shows those SI to be thermosensitive at 90 9C for 45 min and stable within the pH range of 3,0 at 9,0 for 15 min. Antibiotic activity of the substances against Vibrio angufflarum NCMB 2133, V anguillarum ATCC 19264 and Aeromonas salmonicida 76,79 was comparatively equivalent to 30 ppm of the antibiotic oxitetraciclina (OTC).